Role of Genetic Alterations in the NLRP3 and CARD8 Genes in Health and Disease - G. V. Paramel; A. Sirsjö; K. Fransén (Mediators of Inflammation)
The complexity of a common inflammatory disease is influenced by multiple genetic and environmental factors contributing to the susceptibility of disease. Studies have reported that these exogenous and endogenous components may perturb the balance of innate immune response by activating the NLRP3 inflammasome. The multimeric NLRP3 complex results in the caspase-1 activation and the release of potent inflammatory cytokines, like IL-1β. Several studies have been performed on the association of the genetic alterations in genes encoding NLRP3 and CARD8 with the complex diseases with inflammatory background, like inflammatory bowel disease, cardiovascular diseases, rheumatoid arthritis, and type 1 diabetes. The aim of the present review is therefore to summarize the literature regarding genetic alterations in these genes and their association with health and disease.